2015
DOI: 10.1039/c5cc03190g
|View full text |Cite
|
Sign up to set email alerts
|

Highly open rhombic dodecahedral PtCu nanoframes

Abstract: Herein, we report a facile strategy that allows one-pot preparation of highly open rhombic dodecahedral PtCu alloy nanoframes. Due to the highly open structures, the PtCu nanoframes exhibit enhanced catalytic performance in methanol electrooxidation, showing a new strategy to create highly active catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 41 publications
(66 reference statements)
2
70
0
Order By: Relevance
“…[ 189 ] Shido and Iwasawa concluded that the intermediate for the WGS was a bidentate formate, formed by the reaction of CO with terminal hydroxyl groups on CeO 2 , and that the subsequential decomposition of the bidentate formate to a unidentate carbonate and H 2 is considered as the rate determining step. [ 190 ] However, the variable mechanisms are strongly dependent on the choice of experimentations, thus the dominant mechanism and surface intermediate should be in association with the experimental conditions for a specifi c catalyst. Therefore, Burch put forward a universal mechanism for the forward and reverse WGS reactions shown in Figure 41 to rationalize the apparent discrepancies between different models.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…[ 189 ] Shido and Iwasawa concluded that the intermediate for the WGS was a bidentate formate, formed by the reaction of CO with terminal hydroxyl groups on CeO 2 , and that the subsequential decomposition of the bidentate formate to a unidentate carbonate and H 2 is considered as the rate determining step. [ 190 ] However, the variable mechanisms are strongly dependent on the choice of experimentations, thus the dominant mechanism and surface intermediate should be in association with the experimental conditions for a specifi c catalyst. Therefore, Burch put forward a universal mechanism for the forward and reverse WGS reactions shown in Figure 41 to rationalize the apparent discrepancies between different models.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…To date, various bimetallic PtM materials with different structures and compositions have been demonstrated. For instance, PtPd nanoicosahedrons [13], hollow PtPd nanoparticles [14], rhombic dodecahedral PtCu nanoframes [15], Au@Porous Pt yolk-shell nanoparticles [16], PtPd nanodendrites [17] and AuPt alloyed flowerlike - assembly nanochains [18] have been obtained by different synthetic routes. Generally, control of shapes, composition and surface structures of the nanoparticles can help improve materials’ catalytic properties [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…Dendrite and branch structures not only exhibit large surface area and high active sites, but also significantly relieve the aggregation happened in electrocatalytic stability test [9,33,34]. Highly open noble metal nanocages and nanoframes exhibit enhanced electrocatalytic properties due to their three-dimensional accessible surface atoms [20,35,36]. A nanosegregated noble metal skin on these open structures can further improve the catalytic performance [18,37].…”
Section: à2mentioning
confidence: 99%
“…In the past decade, various experimental methods have been developed to synthesize sizedependent, high catalytic performance noble metal-based nanocomposites with diverse morphologies, such as polyhedron, concave, wire, plate, belt/ribbon, dendrite/branch and cage/frame structures [9][10][11][12][13][14][15][16][17][18][19][20][21]. Smaller size means higher surface-area-to-volume ratio, higher atomic utilization efficiency and more catalytic active sites.…”
Section: à2mentioning
confidence: 99%